Dynamic and static structural responses of the spent nuclear fuel disposal canister due to the accidental drop and impact on to the ground. Issue 1 (1st January 2017) - Kwon, Young Joo
Abstract: In this paper, dynamic and static structural responses of the spent nuclear fuel disposal canister for PWR due to the accidental drop and impact on to the ground are analyzed in a multidisciplinary analysis manner theoretically and numerically in order to ensure the structural durability of the canister. The impact impulse occurring by the frictionless contact collision between the canister and the ground is studied theoretically and the numerical analysis on the dynamic response is presented to compute the impact load and other dynamic features incurred during the collision. The static structural impact response occurring in the canister is also analyzed numerically using the nonlinear finite element analysis technique.